THE ECONOMIC VALUE OF TRIFOLIUM REPENS L. (PALL.) FROM THE FABACEAE LINDL FAMILY. WILD RELATIVES OF CULTIVATED PLANTS OF THE REPUBLIC OF KARAKALPAKSTAN - Almenova Gulbanu; Yuldasheva Lobarxon (Journals Park Publishing, 2023)
The article describes the economic value of Trifolium repens L. A moisture-loving and light-loving winter-hardy plant that grows well on soils of different fertility. It grows in the valley and delta of the Amu Darya; it is found along the banks of ditches, in gardens, damp wetlands, as well as among crops. Geographic type: Paleoarctic. It is a valuable plant, it is used as a medicinal, food, industrial, fodder and melliferous plant.
Keywords: Wild relatives of cultivated plants, flora, Trifolium repens L., Fabaceae Lindl.